2020
DOI: 10.1111/eci.13457
|View full text |Cite
|
Sign up to set email alerts
|

Factors influencing oral anticoagulant use in patients newly diagnosed with atrial fibrillation

Abstract: Background: We investigated factors that influenced oral anticoagulant (OAC) initiation and choice in Australian general practice patients newly diagnosed with AF. Methods: Using an Australian nationally representative general practice dataset, MedicineInsight, we identified patients newly diagnosed with AF between January 2009 and April 2019. Logistic regression analyses were used to examine factors associated with OAC initiation and choice. Results: A total of 63 212 patients with AF (53.7% males, mean age 7… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 39 publications
0
15
0
Order By: Relevance
“…Possible reasons for not prescribing an OAC in patients with high stroke risk, including high bleeding risk, frailty, use of antiplatelet agents, and dementia, are found elsewhere 29,30 . In our recent study using the MedicineInsight data set, we found that high risk of bleeding, having a recorded history of dementia or liver disease and female sex were independently associated with not being prescribed with an OAC 20 . A recent study by Steinberg et al found that almost one‐third of patients with high stroke risk and not prescribed an OAC had at least 1 major contraindication to OAC use; high bleeding risk was the most common contraindication.…”
Section: Discussionmentioning
confidence: 84%
See 3 more Smart Citations
“…Possible reasons for not prescribing an OAC in patients with high stroke risk, including high bleeding risk, frailty, use of antiplatelet agents, and dementia, are found elsewhere 29,30 . In our recent study using the MedicineInsight data set, we found that high risk of bleeding, having a recorded history of dementia or liver disease and female sex were independently associated with not being prescribed with an OAC 20 . A recent study by Steinberg et al found that almost one‐third of patients with high stroke risk and not prescribed an OAC had at least 1 major contraindication to OAC use; high bleeding risk was the most common contraindication.…”
Section: Discussionmentioning
confidence: 84%
“…29,30 In our recent study using the MedicineInsight data set, we found that high risk of bleeding, having a recorded history of dementia or liver disease and female sex were independently associated with not being prescribed with an OAC. 20 A recent study by Steinberg et al found that almost one-third of patients with high stroke risk and not prescribed an OAC had at least 1 major contraindication to OAC use; high bleeding risk was the most common contraindication. However, the use of an OAC in these patients was associated with lower rates of all-cause stroke, hospitalisation and mortality but with a higher risk of intracranial haemorrhage.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It is the largest de‐identified Australian general practice database available to researchers. Details about the MedicineInsight dataset are available elsewhere 6–9 . Patients aged 18 years or older with at least three visits to their general practice in the previous 2 years and a recorded diagnosis of AF before the census time were included.…”
Section: Figurementioning
confidence: 99%